An Improved and Efficient Synthesis of Panobinostat. (September 2018) - Chen, Shanwen; Zhang, Peiming; Chen, Huali; Zhang, Pu; Yu, Yu; Gan, Zongjie
An improved and efficient method for the synthesis of panobinostat was developed. The commercially available starting material 4-(chloromethyl)benzaldehyde was converted to ( E )-methyl 3-[4-(chloromethyl)phenyl]acrylate via the Wittig–Horner reaction and was then directly condensed with 2-(2-methyl-1 H -indol-3-yl)ethanamine to afford the key intermediate ( E )-methyl 3-[4-({[2-(2-methyl-1 H -indol-3-yl)ethyl]amino}methyl)phenyl]acrylate in a one-pot synthesis reactor. Subsequently a nucleophilic substitution reaction was carried out smoothly to generate the desired compound. The key intermediate and target compound were characterised by HRMS, 1 H NMR and 13 C NMR. This procedure is operationally simple and would be more suitable for industrial production.